Multipoint Observations of Magnetic Reconnection in the Martian Magnetotail Triggered by an Interplanetary Magnetic Field Rotation - Yuanzheng Wen; Jasper S. Halekas; Han-Wen Shen; Abigail R. Azari; David A. Brain; Yaxue Dong; David L. Mitchell; Christian X. Mazelle; Jared R. Espley; James P. McFadden (The Astrophysical Journal Letters)
The induced magnetosphere of Mars is highly dynamic, driven by both the upstream solar wind and the planet’s crustal magnetic fields. This variability can occur on timescales much shorter than a single spacecraft orbit, making it difficult to distinguish between spatial and temporal variations in the induced magnetosphere. In this study, we utilize simultaneous multipoint observations from the Mars Atmosphere and Volatile EvolutioN (MAVEN) and Tianwen-1 missions to investigate how the induced magnetosphere responds to dynamic changes in the solar wind. We report a magnetic reconnection event observed by MAVEN in the Martian magnetotail, occurring a few minutes after an interplanetary magnetic field (IMF) rotation observed by Tianwen-1 in the upstream solar wind. This reconnection event is characterized by clear Hall magnetic field signatures and high-speed ion jets, indicating the presence of a diffusion region. Our analysis of the change in the magnetic field morphology suggests that this reconnection was likely triggered by this IMF rotation, occurring during the resulting reconfiguration of the induced magnetosphere. This multipoint study demonstrates the important role of dynamic upstream solar wind conditions, particularly IMF rotations, in driving the plasma processes in the Martian magnetotail, contributing to our understanding of solar wind energy and momentum transfer and their roles in ion escape in Mars’s hybrid magnetosphere.